Well‐Defined Ni(0) and Ni(II) Complexes of Bicyclic (Alkyl)(Amino)Carbene (MeBICAAC): Catalytic Activity and Mechanistic Insights in Negishi Cross‐Coupling Reaction. Issue 59 (23rd August 2022) - Thakur, Sandeep Kumar; Kaur, Mandeep; Manar, Krishna Kumar; Adhikari, Manu; Choudhury, Angshuman Roy; Singh, Sanjay
Abstract: Negishi cross‐coupling reaction of organozinc compounds as nucleophiles with aryl halides has drawn immense focus for C−C bond formation reactions. In comparison to the well‐established library of Pd complexes, the C−C cross‐coupling of this particular approach is largely primitive with nickel‐complexes. Herein, we describe the syntheses of Ni(II) complexes, [( Me BICAAC)2 NiX2 ] (X=Cl (1 ), Br (2 ), and I (3 )) by employing the bicyclic (alkyl)(amino)carbene ( Me BICAAC) ligand. The reduction of complexes 1 –3 using KC8 afforded the two coordinate low valent, Ni(0) complex, [( Me BICAAC)2 Ni(0)] (4 ). Complexes 1 –4 have been characterized by spectroscopic techniques and their solid‐state structures were also confirmed by X‐ray crystallography. Furthermore, complexes 1 –4 have been applied in a direct and convenient method to catalyze the Negishi cross‐coupling reaction of various aryl halides with 2, 6‐difluorophenylzinc bromide or phenylzinc bromide as the coupling partner in the presence of 3 mol % catalyst. Comparatively, among all‐pristine complexes, 1 exhibit high catalytic potential to afford value‐added C−C coupled products without the use of any additive. The UV‐vis studies and HRMS measurements of controlled stochiometric reactions vindicate the involvement of Ni(I)−NI(III) cycle featured with a penta‐coordinated Ni(III)‐aryl species as the key intermediate for 1 whereas Ni(0)/Ni(II) species are potentially involved in the catalytic cycle of 4 . Abstract : A wide range of aryl halides were coupled with phenylzinc bromides in Negishi cross‐coupling reaction catalyzed by Me BICAAC‐nickel complexes. The active species are deciphered by means of UV‐vis, HRMS and NMR measurements and support the involvement of Ni(I)/Ni(III) species in the reaction promoted by [( Me BICAAC)2 Ni II Cl2 ] pre‐catalyst whereas, Ni(0)/Ni(II) cycle operates when the Ni(0) complex, [( Me BICAAC)2 Ni 0 ] was used as pre‐catalyst.